KETERKAITAN ANTARA KEMAMPUAN MEMAAFKAN DAN KEBAHAGIAAN REMAJA DENGAN ORANG TUA BERCERAI - Hartini, Nurul (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
This study aims to determine the relationship between forgiveness and happiness in adolescents who have divorced parents. This study uses a quantitative approach using survey data collection methods. The subjects of this study were teenagers with an age range of 15-23 years, both male and female who had divorced parents with a total of 114 subjects. The measuring instrument used in this study to measure forgiveness is TRIM-18 (Transgression-Related Interpersonal Motivations Inventory) developed by McCullough et al. (2006) which has been adapted by (Umar M. F., 2016). Meanwhile, the measuring tool used for happiness is The Oxford Happiness Questionnaire (OHQ) developed by Hills & Argyle (2002) which has been modified and adapted by (Sartika, 2018). The results of the study were analyzed using Product Moment from Pearson correlation. The results of data analysis show that there is a significant positive relationship between forgiveness and happiness in adolescents who have divorced parents, with a correlation coefficient of r = 0.362 with p = 0.000. This indicates that the higher the forgiveness, the higher the level of happiness in adolescents who have divorced parents. Conversely, the lower the forgiveness, the lower the level of happiness in adolescents whose parents are divorced.